Implementation of Sanctions in Regional Regulation Number 2 Year 2020, Gowa District Perspective Saddu Zari'ah - Talli, Abdul Halim (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2021)
The Gowa Regency Government enforces Regional Regulation No. 2/2020 concerning Mandatory Masks and Implementation of Health Protocols in Preventing the Spread of Corona Virus Disease 2019 on September 21, 2020. The enactment of this regional regulation has drawn a lot of criticism and protests from the public, especially those who have been caught in the operation of law enforcement. The bylaw is interesting to study further for reasons. First, this regional regulation was born and enforced for people affected by Covid-19 who feel the impact in various aspects of life. Second, the spread of the 2019 corona virus disease is determined by the Central Government as a non-natural national disaster, therefore the regulations governing it are also stipulated by the Central Government. This study is viewed from two aspects, namely: 1) What is the legal position of Perda No. 2 of 2020 Gowa Regency according tao the laws and regulations in Indonesia? and 2) What is the saddu zari'ah perspective on the enforcement of the sanctions in the perda? This study is expected to provide insight regarding the legal position of Perda No. 2 of 2020, Gowa Regency, as well as revealing the saddu zari'ah perspective on the imposition of sanctions in the perda. This discussion uses a juridical-syar'iy approach. This study shows that Regional Regulation Number 2 of 2020 Gowa Regency is legal and binding in accordance with the applicable laws and regulations. The Perda fulfills the formal and material requirements in the formation of legislation in Indonesia. Meanwhile, the saddu zari'ah perspective on the imposition of sanctions in this regional regulation is in accordance with the Shari'a, because the imposition of sanctions leads people to comply with the obligation to wear masks and implement health protocols to avoid and control the transmission of covid-19.